2018
DOI: 10.4103/jisp.jisp_382_18
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent gingival cyst of adult: A rare case report with review of literature

Abstract: The gingival cyst of adult (GCA) is a rare developmental anomaly of odontogenic origin. It is asymptomatic, slow growing, and commonly seen near the canine and premolar region of mandible. The GCA is usually treated by excisional biopsy. Usually, occurrence is more common in 5th to 6th decade of life. The present case report describes a solitary GCA treated by excisional biopsy in a 76-year-old male patient which had recurred for the fourth time. This article also highlights on diagnostic process and a review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…GCAs are rare developmental lesions, with about 170 cases described in the literature over the past 70 years worldwide [ 2 , 8 , 12 , 13 ]. Unfortunately, in most studies, they are only cited among odontogenic cysts or as a subgroup without providing a detailed description of each case's characteristics [ 6 , 10 , 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCAs are rare developmental lesions, with about 170 cases described in the literature over the past 70 years worldwide [ 2 , 8 , 12 , 13 ]. Unfortunately, in most studies, they are only cited among odontogenic cysts or as a subgroup without providing a detailed description of each case's characteristics [ 6 , 10 , 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…GCAs are treated by simple excision with minimal margin involvement and submitted for histopathological examination to establish the diagnosis, with usually no tendency to recur [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…GCAs have been described in the literature for over 70 years, though, as pointed out by Frigerio et al in their study, they have been reported as odontogenic cysts or as a subcategory without a detailed description [3,18]. Ritchey and Orban were the first to study a GCA as an independent lesion, though it was considered a histological entity without clinical interest [19].…”
mentioning
confidence: 99%